Seismic Improvement and Rehabilitation of Steel Concentric Braced Frames: A Framework-Based Review - Atefeh Soleymani; Hamed Saffari (Journal of Rehabilitation in Civil Engineering)
The ability of structures to withstand seismic loads is the most important feature of earthquake engineering. Because of their high stiffness and lateral strength, concentrically braced frames (CBF) are one of the most prevalent resisting methods in engineering structures. Under moderate seismic events, CBFs have limited lateral displacement capability, resulting in structural damage and substantial post-earthquake expenses. However, when these constructions are exposed to moderate to severe seismic events, their compression members start to buckle. Buckling these compression members in CBF also reduces ductility and causes hysteresis curve deterioration. As a result, they become brittle and have a limited capacity to dissipate seismic energy. On the other hand, conventional CBF constructions exposed to seismic hazards may display an unacceptable soft-story mechanism, in which drift and damage are localized in a single-story, while all the other stories are comparatively unscathed. Several research works have improved CBF seismic behavior, and different strategies have resulted in seismic improvement. This paper presented an overview of seismic improvement modifications of CBF, which have been studied in the literature. A review of current studies to better understand and analyze CBF behavior is presented.